Synthesis, characterization and catalytic activity of Mn(III)- and Co(II)-salen complexes immobilized mesoporous alumina - Chaube, V. D.; Shylesh, S.; Singh, A. P. (Journal of Molecular Catalysis A-Chemical, 2005)
Mn(III) and Co(II)-schiff base complexes were immobilized over mesoporous alumina through the reaction of mesoporous alumina functionalized 3-aminopropyl triethoxy silane (3-APTES) and salicylic aldehyde via schiff base condensation. The surface properties of the functionalized catalysts were analyzed by a series of characterization techniques like elemental analysis, PXRD, FTIR, N(2) adsorption-desorption, TG-DTG, DR UV-vis, XPS, etc. PXRD and adsorption-desorption analysis shows that the mesostructure of alumina remains intact after various modifications, while spectral technique show the successful anchoring of the neat complexes inside the porous alumina support. The catalytic activity of the functionalized metal-salen complexes examined in the liquid phase oxidation of styrene and cyclohexene shows that the functionalized salen complexes are more active and selective than the corresponding neat metal complexes. Further, the catalyst (Mn-S-NH(2)-MA) was recycled three times in the oxidation of styrene and no major change in the conversion and selectivity is observed, which shows that the immobilized metal-salen complexes are stable under the present reaction conditions. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Immobilization; Mesoporous alumina; Oxidation; Schiff base complexes

Sulfonic acid functionalized mesoporous silicas and organosilicas: synthesis, characterization and catalytic applications - Shylesh, S.; Samuel, Prinson P.; Srilakshmi, Ch.; Parischa, Renu; Singh, A. P. (Journal of Molecular Catalysis A-Chemical, 2007)
Ethane bridged mesoporous organosilicas and MCM-41 having sulfonic acid groups in the pore channels were prepared by co-condensation method as well as grafting method, using 3-mercaptopropyltriethoxysilane (3-MPTS) as the sulfur precursor. TEM and N-2 sorption isotherm analysis revealed that the mesoporous structural ordering is retained after the functionalization and modifications of organic groups while FT-IR, Raman, XPS and solid-state C-13 CP MAS NMR shows the presence of sulfonic acid groups and the stability of the mesoporous framework. The catalytic activity of the developed materials was evaluated in the liquid phase Claisen-Schmidt condensation reaction of acetophenone with benzaldehyde, to probe the effect of mesoporous support surfaces as well as the role of preparation methods. Results showed that sulfonic acid functionalized ethane-silica samples were more active, selective and stable than the conventional sulfonic acid containing mesoporous catalysts. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: condensation; ethane-silica; heterogeneity; sulfonic acids

Synthesis of hydrothermally stable aluminium-containing ethane-silica hybrid mesoporous materials using different aluminium sources - Shylesh, S.; Samuel, Prinson P.; Singh, A. P. (Microporous and Mesoporous Materials, 2007)
Aluminium-containing ethane-silica hybrid mesoporous materials having ethane groups in the frame wall positions are synthesized using aluminium isopropoxide as well as aluminium nitrate as the aluminium sources. The materials were characterized in detail using powder XRD, N-2 adsorption-desorption, SEM, TEM, TG-DTG, TPD, Si-29, C-13 and Al-27 MAS NMR techniques. Characterization techniques revealed that aluminium isopropoxide was the appropriate source for the synthesis of organo aluminosilicas on considering the structural ordering, acidity as well as the percentage of aluminium incorporation into the ethane bridge. Al-27 MAS NMR displays aluminium as tetrahedrally coordinated in both the aluminium-containing organosilicas. Unlike the conventional EtOH-HCl template extraction process, in the present studies, we had used EtOH-NH4OH as the surfactant-extracting medium and chemical analysis results suggest that using this procedure the extent of dealumination can be greatly reduced. XRD and nitrogen physisorption studies further proved that the materials are hydrothermally stable, that the ordered pore channels retains its structure even after 150 h reflux in boiling water, while the conventional Al-MCM-41 catalyst collapsed its mesostructure after 50 h reflux in water. The improved hydrothermal stability of the hybrid materials, even in presence of sodium ions, is attributed to the thick pore walls as well as due to the presence of hydrophobic bridging ethane groups in the wall positions. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: Al-HMM; Al-MCM-4l; hybrid materials; Hydrothermal stability

Synthesis and characterization of bifunctional ethenylene bridged mesoporous organoaluminosilicates - Shylesh, S.; Kapoor, Mahendra P.; Juneja, Lekh R.; Srilakshmi, Ch.; Singh, A. P. (Nanoscience and Nanotechnology Letters, 2011)
Bifunctional mesoporous organosilicas having -CH=CH- bridges and aluminium in tetrahedral coordination with tailorable pore sizes have been synthesized using a one-step templating method using cationic surfactants of different chain lengths. Unlike the conventional EtOH-HCl template extraction process, EtOH-NH(4)NO(3) was used as the surfactant-extracting medium and chemical analysis results suggest that through this procedure the mesoporous structure can be retained and dealumination can be minimized. The surfactant-extracted mesoporous solids display high surface area, pore volume and the pore size of the material varies in the range 2.6-3.6 nm, with respect to the alkyl chain length of the cationic surfactant. XRD and nitrogen physisorption studies further proved that the organosilicas are hydro thermally stable than the conventional Al-MCM-41 materials and their better stability is attributed to the thick pore walls as well as due to the presence of hydrophobic bridging ethenylene groups in the wall positions. The coupling of Al(4) with -CH=CH- bridges offer new prospects for the application of periodic mesoporous organosilicas in heterogeneous catalysis.
Keywords: Aluminium; Cationic Surfactants; Hydrothermal stability; Organosilicas

Synthesis and characterization of 3-[N,N `-bis-3-(salicylidenamino)ethyltriamine] Mo(VI)O-2@SBA-15: a highly stable and reusable catalyst for epoxidation and sulfoxidation reactions - Lazar, Anish; Thiel, Werner R.; Singh, A. P. (RSC Advances, 2014)
The efficient and reusable oxidation catalyst 3-[N,N'-bis-3-(salicylidenamino)ethyltriamine] Mo(VI)O-2@SBA-15 has been synthesized by the anchoring of the 3-[N,N-bis-3-(salicylidenamino)ethyltriamine] ligand (L or Salpr) on the inner surfaces of organofunctionalized SBA-15 and subsequent complexation with Mo(VI) O-2(acac)(2). The physico-chemical properties of the functionalized catalysts were analyzed by elemental analysis, ICP-OES, XRD, N-2-sorption measurements, TG & DTA, solid state C-13, Si-29 NMR spectroscopy, FT-IR, Raman spectroscopy, XPS, DRS UV-Vis spectroscopy, SEM and TEM. XRD and N-2 sorption analyses helped to find out the morphological and textural properties of the synthesized catalysts and confirm that an ordered mesoporous channel structure was retained even after the multistep synthetic procedures. The (100), (110) and (200) reflections in SBA-15 provide hints of a good structural stability, the existence of long range ordering and a high pore wall thickness. TG and DTA results reveal that the thermal stability of (L)Mo(VI)O-2@SBA-15 was maintained up to 300 degrees C. The organic moieties anchored over the surface of the SBA-15 support were determined by solid state C-13 NMR and FT-IR spectroscopy. Further, solid state Si-29 NMR spectroscopy provides the information about the degree of functionalization of the surface silanol groups with the organic moiety. The electronic environment and the oxidation state of the molybdenum site in (L)Mo(VI)O-2@SBA-15 were monitored by Raman spectroscopy, XPS and DRS UV-Vis techniques. Moreover, the morphology and topographic information of the synthesized catalysts were confirmed by SEM and TEM imaging. The synthesized catalysts were evaluated in epoxidation and sulfoxidation reactions, and the results show that (L)Mo(VI)O-2@SBA-15 exhibits high conversion and selectivity towards epoxidation and sulfoxidation reactions in combination with high stability. The anchored solid catalysts can be recycled effectively and reused several times without major loss in activity. In addition, Sheldon's hot filtration test was also carried out.

Synthesis of a recyclable and efficient Pd(II) 4-(2-pyridyl)-1,2,3-triazole complex over a solid periodic mesoporous organosilica support by ``click reactions'' for the stille coupling reaction - Sharma, Priti; Singh, A. P. (RSC Advances, 2014)
A highly efficient, reusable B-PMO-TZ-Pd(II) catalyst was synthesized by anchoring 4-(2-pyridyl)-4-(2-pyridyl)-1,2,3-triazole ligand over the surface of an organo-functionalized benzene support containing periodic mesoporous organosilica (B-PMO) via ``click reaction'' and the subsequent complexation with PdCl2. B-PMO materials with uniform hexagonal arrangements were prepared using C-16 alkyl trimethyl ammonium bromide [CTAB] surfactant under basic conditions. The physiochemical properties of the functionalised catalyst were analysed by elemental analysis, ICP-OES, XRD, N-2 sorption, TGA & DTA, solid state C-13, Si-29 NMR spectra, FT-IR, XPS, UV-vis, SEM and TEM. XRD and N-2 sorption revealed the morphological and textural properties of the synthesized catalyst, confirming that ordered mesoporous channel structure was retained even after the multistep synthetic procedure. The (100), (110) and (200) reflections in B-PMO are evidence of its good structural stability and the existence of long range order. The TGA-DTA results reveal that the synthesized catalyst B-PMO-TZ-Pd(II) was thermally stable, even at high temperature. The organic moieties anchored over the surface of B-PMO were demonstrated by solid state C-13 NMR and FT-IR spectroscopy. Solid state Si-29 NMR spectroscopy provides information about the degree of functionalization of the surface silanol group. The electronic environment and oxidation state of Pd in B-PMO-TZ-Pd(II) were monitored by XPS and UV-visible techniques. Moreover, the morphologies and topographic information of the synthesized B-PMO-TZ-Pd(II) catalyst were confirmed by SEM and TEM analyses. The catalytic properties of the catalyst for the Stille coupling reaction were screened, and higher catalytic activities with high TONs were observed. The anchored solid B-PMO-TZ-Pd(II) catalyst can be recycled efficiently and reused several (four) times without a major loss in reactivity.

Synthesis and characterization of nanoporous silica SBA-15 diaminocyclohexane and its application in removal of Cu(II) and Ni(II) from aqueous solution - Sreenu, Bhogineni; Sharma, Priti; Seshaiah, Kalluru; Singh, A. P. (Desalination and Water Treatment, 2016)
A new nanoporous 1,2-diaminocyclohexane-functionalized SBA-15 (Dach@SBA-15) silica sorbent was prepared. The structure and physicochemical properties of the material were characterized by elemental analysis, X-ray diffraction, transmission electron microscopy (TEM), scanning electron microscopy, FT-IR spectroscopy, nitrogen adsorption-desorption isotherms and thermogravimetric analysis. TEM image clearly showed the sheet-like structure of Dach@SBA-15. The organic functional groups were successfully grafted onto the SBA-15 surface and the ordering of the support was not affected by the chemical modification. The Dach@SBA-15was used as a sorbent for removal of Cu(II) and Ni(II) from aqueous solution. Experimental parameters like effect of pH, contact time and metal ion concentration were studied and optimized. The adsorption isotherm data fitted well to Langmuir isotherm model and the monolayer adsorption capacity values for Cu(II) was 90.09 and for Ni (II) was 84.03 mg/g at 303 K. The experimental kinetic data fitted very well to the pseudosecond- order model. The Dach@SBA-15 could be used as a sorbent for removal of Cu(II) and Ni(II) from aqueous medium.
Keywords: Adsorption; BET; FAAS; FT-IR; Heavy metals; Nanoporous silica

Synthesis of new hybrid sorbent 2-mercaptobenzaldehyde SBA-15 and its application in solid phase extraction of Cd(II) from water and food samples - Sreenu, B.; Imran, K.; Seshaiah, K.; Sharma, Priti; Singh, A. P. (Analytical Methods, 2016)
In this paper, a new mesoporous hybrid material was fabricated by anchoring 2-mercaptobenzaldehyde (2MB) onto the surface of SBA-15. The adsorbent (2MB-SBA-15) was characterized by Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), nitrogen adsorption-desorption isotherm measurements and thermogravimetric analysis (TGA) and applied as a sorbent in the preconcentration of Cd(II) in water samples and food samples. The effect of various analytical parameters such as pH, dose of sorbent, amount of eluent, sample flow rate and interfering ions was investigated. The preconcentration capacity of the prepared material under optimized conditions for Cd(II) was 0.94 +/- 0.01 mmol g(-1). The Cd collected onto the sorbent was eluted out with 10 mL of 1 M HNO3 and determined by AAS. The LOD, LOQ and preconcentration factor of the present method were found to be 6.93 x 10(-6), 1.21 x 10(-5) mM and 100, respectively. The relative standard deviation for four preconcentration experiments was found to be <= 5%.

Synthesis and characterization of D-2PA-Pd(II)@SBA-15 catalyst via ``click chemistry'': highly active catalyst for Suzuki coupling reactions - Pathak, Aruna; Singh, A. P. (Journal of Porous Materials, 2017)
Copper catalysed cycloaddition reaction between azide and terminal alkyne, called as ``click reaction'', was found to be modular approach for the synthesis of facile, highly efficient and recoverable D-2PA-Pd(II)@SBA-15 catalyst. In efforts to synthesize the catalyst, the cycloaddition reaction between azido-functionalized mesoporous SBA-15 and N,N-dimethyl-2-propynylamine (D-2PA) has been carried out, followed by the complexation with PdCl2. To analyze physiochemical properties of synthesized materials, various characterization techniques such as CHN elemental analysis, X-ray diffraction, solid state C-13 and Si-29 NMR spectra, FT-IR, XPS, SEM, TEM and N-2 sorption analysis, TGA and DTA, UV-Vis spectroscopy have been carried out. The synthesized catalyst, D-2PA-Pd(II)@SBA-15, exhibited excellent catalytic activities with good product yield and high TON towards Suzuki coupling reaction of various aryl halides with phenylboronic acid. The effect of solvent, base and temperature on coupling reactions has also been described. The developed protocol offers recyclability of catalyst for multiple (four) times without any appreciable loss in stability and catalytic reactivity.
Keywords: Click reaction; Cycloaddition; mesoporous materials; SBA-15; Suzuki coupling

Synthesis of heterogeneous Ru(II)-1,2,3-triazole catalyst supported over SBA-15: application to the hydrogen transfer reaction and unusual highly selective 1,4-disubstituted triazole formation via multicomponent click reaction - Sharma, Priti; Rathod, Jayant; Singh, A. P.; Kumar, Pradeep; Sasson, Yoel (Catalysis Science & Technology, 2018)
In the present study, we demonstrate a simple and efficient method for ligand formation and covalent anchoring to a heterogeneous support via click reaction. The complex tris(triphenylphosphine) ruthenium(II) dichloride [RuCl2(PPh3)(3)] anchored over the click modified ligand of SBA-15 forms a new highly efficient heterogeneous SBA-15-Tz-Ru(II) TPP catalyst. Solid state C-13, Si-29, and P-31 CP-MAS NMR spectra provide evidence for the formation of the heterogeneous catalyst. SBA-15-Tz-Ru(II) TPP catalyst was screened for the multicomponent click cycloaddition reaction in water medium as a green solvent and it exhibited unusual and excellent selectivity for the formation of 1,4-disubstituted triazole product under mild reaction condition. In addition, SBA-15-Tz-Ru(II) TPP catalyst also catalyzed the hydrogen transfer reaction of various carbonyl compounds with excellent catalytic activity to give the corresponding alcohols. The heterogeneous catalyst can be recycled and reused several times (five) without a loss in reactivity.